A fast phase tracking reference-less all-digital CDR circuit for human body channel communication. (February 2019) - Chung, Ching-Che; Sheng, Duo; Li, Ming-Chieh; Tsai, Yi-Che
Abstract: This paper presents a fast phase tracking and reference-less all-digital clock and data recovery circuit (ADCDR) for body channel communication (BCC) applications. The proposed ADCDR uses the novel phase-error calculation without a reference clock signal to improve the phase-tracking ability and reduce overall power consumption by eliminating the requirement for an external quartz crystal oscillator. In addition, the proposed gain-calibration method can automatically calibrate the gain value under different process-voltage-temperature (PVT) conditions to quickly compensate for the phase error. The wideband signaling (WBS) transceiver, including the proposed ADCDR is implemented using a 90-nm CMOS process with a core area of 0.36 mm 2 . The maximum transmission data rate of the proposed design is 20 Mb/s and power consumption is 2.2 mW, which are very suitable for the wearable device applications as compared with the traditional designs.